Effects of dietary soybean lecithin on gonadal development and vitellogenin mRNA expression in the female redclaw crayfish Cherax quadricarinatus (von Martens) at first maturation. Issue 8 (26th March 2012) - Wang, Lanmei; Zuo, Di; Lv, Weiwei; Li, Jiayao; Wang, Qun; Zhao, Yunlong
Abstract: The effect of increasing levels of dietary de‐oiled soybean lecithin (SL) on the ovarian development of female redclaw crayfish, Cherax quadricarinatus, was investigated. Five practical formulated diets were supplemented with 0% (Diet 1), 1% (Diet 2), 2% (Diet 3), 4% (Diet 4) and 6% (Diet 5) SL. Crayfish (initial weight: 25.64 ± 1.53 g) were fed each diet in four replicates for 8 weeks. Crayfish that were fed diets containing ≥2% SL had a significantly higher gonadosomatic index than those fed with Diets 1 and 2 ( P < 0.05), while hepatosomatic index showed a decreasing trend ( P > 0.05). The fatty acid composition of the hepatopancreas is largely due to the dietary composition. Higher dietary SL yielded a higher percentage of ovarian polyunsaturated and highly unsaturated fatty acids ( P < 0.05). Furthermore, the higher content of linoleic acid and alpha linolenic acid in diets may be more important for ovarian development in C. quadricarinatus, as these originate from the hepatopancreas. The hepatopancreatic vitellogenin mRNA expression was the highest in crayfish that received Diet 3. Our results suggest that dietary SL has a positive effect on ovarian development in C. quadricarinatus broodstock, and at least 2% SL should be supplemented in broodstock diets to enhance ovarian maturation during aquaculture.